Effectiveness of nonsurgical antibiotic treatment in the experimental appendicitis model in rats - Halis Can Demirtürk; Halil Ibrahim Tanriverdi; Fatma Taneli; Semin Ayhan; Cüneyt Günşar (SpringerOpen, 2022)
Abstract Background In this study, we aimed to demonstrate efficacy and laboratory follow-up criteria of nonsurgical antibiotic treatment in uncomplicated acute appendicitis. We established an experimental appendicitis model in rats, and antibiotic treatment was evaluated by biochemical and immunohistochemical changes. Materials and method In the study, 28 rats were divided into 4 groups. Group 1 constituted the group of sham; group 2 was the control group that appendicitis model was created and did not receive any treatment. Group 3 was created as an appendicitis model and was given regular antibiotic treatment. In group 4, appendicitis model was created, and appendectomy was performed on the 2nd day. Blood samples were taken from the rats on the 0, 2nd, and 7th days in all groups. Rats in groups 1, 2, and 3 underwent appendectomy with laparotomy under anesthesia on the 7th day. Serum C-reactive protein (CRP), procalcitonin, and leukocyte levels were measured for biochemical analysis. In immunohistochemical evaluation, inflammation severity of the tissue samples taken from appendices was evaluated. Also, tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) levels of tissue samples were evaluated. Results A statistically significant difference in CRP values was observed between groups 1 and 2 on the 7th day (p = 0.046), between groups 1 and 4 on 0 and 2nd days (p = 0.004, p = 0.004), between groups 2 and 3 on 0, 2nd, and 7th days (p = 0.018, 0.013, 0.025), between groups 2 and 4 on 0, 2nd, and 7th days (p = 0.002, p = 0.002, p = 0.009), and between groups 3 and 4 on 0 and 2nd days (p = 0.013, p = 0.025). There was a significant difference in procalcitonin values between groups 1 and 3 on the 7th day (p = 0.032) and between groups 1 and 4 on day 0 (p = 0.019). A significant difference was also observed in TNF-α and IL-6 inflammation between groups 2 and 3 (p = 0.031, p = 0.018) and between groups 2 and 4 (p = 0.031, p = 0.01). Conclusion Acute uncomplicated and early appendicitis may be treated with antibiotics. According to our results, CRP levels are useful as follow-up criterion in experimental appendicitis model. Clinical studies on the assessment of CRP levels in the course of nonsurgical treatment in the patients with acute appendicitis will reveal out the effectiveness of this marker.